Consolidating the theoretical foundations of digital human resource management acceptance and use research: a meta-analytic validation of UTAUT - Christian Theres; Stefan Strohmeier (Management Review Quarterly, 2023)
With rapid technological progress, the adoption of digital technology in human resource management (HRM) has become a crucial step towards the vision of digital organizations. Over the last four decades, a substantial body of empirical research has been dedicated towards explaining the phenomenon of digital HRM. Moreover, research has applied a wide array of theories, constructs, and measures to explain the adoption of digital HRM in organizations. The results are fragmented theoretical foundations and inconsistent empirical evaluations. We provide a comprehensive overview of theories applied in digital HRM adoption research and propose an adjusted version of the unified theory of acceptance and use of technology as a consolidating theory to explain adoption across settings. We empirically validate this theory by combining evidence from 134 primary studies yielding 768 effect sizes via meta-analytic structural equation modelling. Moderator analyses assessing the influence of research setting and sample on effects show significant differences between private and public sector. Findings highlight research opportunities for future studies and implications for practitioners.
Keywords: O15; C40; M12; 650; Digital HRM; Meta-analysis; e-HRM; Meta-analytic structural equation modeling; UTAUT